Dispositions
X, 458 p.
Keywords: This anthology consists of a collection of papers on the nature of dis positions and the role of disposition concepts in scientific theories. I have tried to make the collection as representative as possible, except that problems specifically connected with dispositions in various special sciences are relatively little discussed. Most of these articles have been previously published. The papers by Mackie, Essler and Trapp, Fetzer (in Section 11), Levi, and Tuomela appear here for the first time, and are simultaneously published in Synthese 34, No. 4, which is a special issue on dispositions. Of the previously published material it should be emphasized that the papers by Hempel and Fisk have been extensively revised specially for this anthology. The papers are grouped in four sections, partlyon the basis of their content. However, due to the complexity of the issues involved, there is considerable overlap in content between the different sections, especially between Sections land 11. I wish to thank Professors James Fetzer and Carl G. Hempel for helpful advicc in compiling this anthology.